2009
DOI: 10.1051/0004-6361/200809643
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site photometry of the pulsating Herbig Ae star V346 Ori

Abstract: Context. The study of pulsation in pre-main-sequence intermediate-mass stars represents an important tool for deriving information about fundamental stellar parameters and internal structure, as well as testing theoretical models. Interest in this class of variable stars has increased significantly during the last decade and about 30 members are presently known in the literature. Aims. After constructing the frequency spectrum of oscillations in V346 Ori, we apply asteroseismic tools to these data to estimate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The spectrum of HD 287841 is consistent with the temperature and gravity determination of Bernabei et al (2009, T eff = 7550 ± 250 K, log g = 3.5 ± 0.4). CS features are only observed in few spectral lines.…”
Section: A57 Hd 287841 (= V346 Ori)supporting
confidence: 79%
“…The spectrum of HD 287841 is consistent with the temperature and gravity determination of Bernabei et al (2009, T eff = 7550 ± 250 K, log g = 3.5 ± 0.4). CS features are only observed in few spectral lines.…”
Section: A57 Hd 287841 (= V346 Ori)supporting
confidence: 79%
“…The microscopic physics, including equation of state, opacities, nucleosynthesis, microscopic diffusion and chemical abundances, is very refined in this stellar evolution code, since this part of the code was tested in the case of the Sun against helioseismic data. The CESAM evolution code is well established in the solar and stellar physics comunity, being used either to compute solar models (Couvidat et al 2003;Berthomieu et al 1993) or models of other stars (among others: PMSδScuti star V346 Ori (Bernabei et al 2009), βChepei star ν Eridani (Suárez et al 2009), 0.8-8M ⊙ PMS and MS stars (Marques et al 2008), Vega-like stars αPsA, βLeo, βPic, εEri and τ Cet (Di Folco et al 2004), αCMi star Procyon A (Kervella et al 2004), solar-like 0.8-1.4M ⊙ stars and PMS stars (Piau & Turck-Chièze 2002), αCen A&B stars (Thévenin et al 2002) and MS stars with convective overshooting (Audard et al 1995)).…”
Section: The Stellar Evolution Codementioning
confidence: 99%
“…Vieira, et al 2003, Pogodin et al 2012) confirmed the classification as a young stellar object. The δ Scuti-like pulsations discovered by Bernabei, et al (2007) were confirmed by Marconi et al (2010), who noted that it could "constrain the poorly sampled red edge of the PMS [pre main sequence] instability strip." The presence of a weak magnetic field in this star is uncertain, as the star was observed only on two different epochs (Wade, et al 2007, Hubrig et al 2009).…”
Section: Gregoriomentioning
confidence: 85%